In vitro Antimicrobial Activity of Cucumis metuliferus E. Mey. Ex. Naudin Fruit Extracts against Salmonella gallinarum - Joy Gararawa Usman; OA Sodipo; UK Sandabe (International Journal of Phytomedicine, 2014)
The fruit of Cucumis metuliferus was collected at Vom, Jos South Local Government Area of Plateau State, this was cleaned, sliced, air dried, pulverised and cold extracted with solvents of different polarities. The (n-hexane, chloroform, methanol and water) extracts of C. metuliferus were tested for in vitro antimicrobial assay against Salmonella gallinarum at varying concentrations, 200 mg/ml to 1000 mg/ml using the disc diffusion method. There was no zone of inhibition by the n-hexane and chloroform extracts at 1000 mg/ml, it was resistant. The methanol extract showed zones of inhibition of 8.33 ± 0.52, 9.67 ± 0.52, 11.67 ± 1.03, 13.67 ± 0.52 and 14.67 ± 0.52 mm at 200, 400, 600, 800 and 1000 mg/ml respectively. The water extract showed zones of inhibition of 7.50 ± 0.55, 8.50 ± 0.55 and 9.67 ± 0.52 mm at 600, 800 and 1000 mg/ml respectively. The zones of inhibition for the standard antibiotics ciprofloxacin 5 µg, chloramphenicol 10 µg and augmentin® 30 µg was 19.33 ± 1.03, 10.66 ± 0.52, 7.33 ±0.52, mm respectively, while tetracycline 30 µg, erythromycin 5 µg, ceftazidime 30 µg and oxacillin 1µg were resistant. The MIC and MBC of 50 mg/ml was recorded for the methanol extract. This study therefore showed that the fruit extracts of Cucumis metuliferus has antimicrobial activity and may probably provide the basis for its use in traditional medicine.